An archaic layer of the Russian Revolution in the ideological field of Russian religious philosophy - E.A. Nagornov (Ученые записки Казанского университета: Серия Гуманитарные науки, 2021)
This paper attempts to find out how the entire preceding course of Russian history predetermined the October Revolution’s outcome. With this aim, the structures and character of the Russian Revolution were analyzed by comparing the basic tenets of the theory of modified inversion cycles of historical development, introduced by the Russian sociologist A.S. Akhiezer, with the philosophical ideas of the representatives of Russian religious philosophy. It was suggested that the dominant Universalist view of revolution, with its idealization, should be replaced by M. Foucault’s singular “intermittent” method. As a result, the ideological affinity between the views of the modern liberal historical project on the Russian Revolution and the basic ideas of the philosophers of the Silver Age of Russian culture was revealed. Particular attention was paid to the “underdeveloped and undisclosed” character of personality in Russia (as understood by N.A. Berdyaev), which manifested itself most clearly in the phenomenon of the Revolution of 1917 and led to the triumph of pre-state and pre-political ideals of a traditional society. The legacy of Russian religious philosophy was reinterpreted by comparing it with the ideas of modern liberal philosophy of history.